Active methods of training in the Maple computer mathematics system - Литвинов, Анатолий Леонидович (Technology audit and production reserves, 2014)
The results of using the Maple computer mathematics system at different stages of a training process are given. One of the routine tasks, faced by teachers, is the accuracy control of completing practical assignments. The task gets more complicated if the solution consists of several stages. Each stage requires sophisticated mathematical transformations, and benchmark data regarding variants must be changed periodically. In the paper, it is suggested applying the Maple system tables. Matrices, procedures for solving equations and graphs can be inserted into the Maple table cells. It allows developing full-featured automated computing systems and monitoring the accuracy of carrying out each stage. In such subjects, like cryptography, it is necessary to perform precise computations with a great scale of whole numbers. The effectiveness of the Maple system when solving the cryptography problem concerning a private key formation over an open channel of communication is showed in the paper. Also, the examples of employing the Maple system as a virtual laboratory are given in the paper. Thus, using the Maple system at different stages of a training process showed its effectiveness as an active educational medium, which allow improving the quality of training.